Public space reader - Mitrašinović, Miodrag, 1965-; Mehta, Vikas, 1966- (Routledge, 2021)
"Recent global appropriations of public spaces through urban activism, public uprising, and political protest have brought back democratic values, beliefs, and practices that have been historically associated with cities. Given the aggressive commodification of public resources, public space is critically important due to its capacity to enable forms of public discourse and social practice which are fundamental for the well-being of democratic societies. Public Space Reader brings together public space scholarship by a cross-disciplinary group of academics and specialists whose essays consider fundamental questions: What is public space and how does it manifest larger cultural, social, and political processes? How are public spaces designed, socially and materially produced, and managed? How does this impact the nature and character of public experience? What roles does it play in the struggles for the just city, and the Right to The City? What critical participatory approaches can be employed to create inclusive public spaces that respond to the diverse needs, desires, and aspirations of individuals and communities alike? What are the critical global and comparative perspectives on public space that can enable further scholarly and professional work? And, what are the futures of public space in the face of global pandemics, such as COVID-19? The readers of this volume will be rewarded with an impressive array of perspectives that are bound to expand critical perspectives on public space"--